Analisis Penerimaan Teknologi (Studi Kasus: Sistem Informasi Akademik STIE Lembah Dempo Pagaralam - Nina Dwi Putriani (Institute of Information Technology and Social Science (IITSS), 2020)
The development of information technology has changed the world to be completely easy, and thanks to the support of computer technology it is proven that the mechanism of long and repetitive work becomes effective and efficient. This study aims to see the acceptance of technology (Academic Information System) in STIE Lembah dempo by using a research model developed by Venkatesh (2003) by ignoring moderator variables. The data in this study were obtained from a questionnaire with a total sample of 230 with freedom of 0.05%, respondents in this study were STIE students. From the results of table 4.14 by looking at the comparison of T-Table and T-Statistic shows that the value of T-Statistics > T-Table so that it can be said that all variables have a positive effect on the acceptance of Academic Information Systems at the high school.